Demographic, clinical, and radiologic signs and treatment responses of lipoid proteinosis patients: a 10-case series from Sanliurfa - Dertlioglu, Selma B.; Calik, Mustafa; Cicek, Demet (Wiley-Blackwell, 2014)
Objectives Lipoid proteinosis (LP) is a rare autosomal recessive genodermatosis characterized by mucocutaneous lesions and hoarseness that develop in early childhood. This paper presents the clinical and radiologic characteristics and treatment responses of 10 LP patients from five different families. Methods Ten LP patients followed in our university clinic in Sanliurfa, Turkey, were evaluated. Clinical features, as well as histopathologic and radiologic findings, were analyzed. Diagnoses were established based on clinical features, with histopathologic confirmation in nine cases. The patients were started on acitretin at a dose of 0.5mg/kg/day for sixmonths. Results Typical cutaneous signs of LP and hoarseness of the voice were observed in all patients. No side effects associated with the drug were found during treatment. At the end of the sixth month, the cutaneous papules and plaques were diminished in seven patients. Hoarseness receded in seven patients (particularly in three), vesiculobullous lesions were reduced in three patients, and the frequency of oral ulcers decreased in three patients. In a patient with palmoplantar hyperkeratosis, lesions were found to disappear completely. Conclusions We believe acitretin is quite effective and reliable in the treatment of cutaneous lesions and hoarseness in patients with LP.
Keywords: Extracellular-Matrix Protein-1; Oral Dimethyl-Sulfoxide; of-the-Literature; Hyalinosis-Cutis; Mucosae; Manifestations; Involvement; Mutations